ANALISIS MINAT BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN JASMANI DI SDN 027 SAMARINDA ULU KOTA SAMARINDA - Andi Alif Tunru Andi Alif; Rahmat Ilahi; Nurul Hikmah (SISTEMA: Jurnal Pendidikan, 2023)
The purpose of this study was to determine the learning interest of Jasamini education students at SD Negeri 027 Samarinda Ulu, Samarinda City. In this research is a type of quantitative descriptive research. Collecting research data by distributing questionnaires that have been provided. The data analysis technique used is simple descriptive statistics using frequency and percentage calculations. The results of this study indicate that students' interest in learning physical education at SDN 027 Samarinda Ulu Samarinda City is high with the highest frequency being in the high category with 19 students or 63.33%. Students' interest in learning physical education at SDN 027 Samarinda Ulu Samarinda City is in the very high category 2 students or 6.67%, the medium category is 6 students or 20.00%, the low category is 10.00% while there is no very low category. And the intrinsic factor has a bigger role than the extrinsic factor which determines students' interest in participating in physical education subjects which can be proven by the very high category frequency on the intrinsic factor of 8 students or 26.67% while on the extrinsic factor of 3 students or 10.00%.